2023
DOI: 10.1111/jdi.13979
|View full text |Cite
|
Sign up to set email alerts
|

Association of acute‐to‐chronic glycemic ratio and outcomes in patients with COVID‐19 and undiagnosed diabetes mellitus: A retrospective nationwide cohort study

Abstract: Aims/Introduction To assess the association of undiagnosed diabetes mellitus and its acute‐to‐chronic glycemic ratio with clinical outcome in patients hospitalized with coronavirus disease 2019 (COVID‐19) using a large‐scale nationwide registry in Japan. Materials and Methods Overall, 4,747 patients were included between July 2021 and January 2022. We evaluated blood glucose and glycated hemoglobin levels at admission, and calculated the acute‐to‐chronic glycemic ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…For example, one study showed that patients with newly diagnosed diabetes who suffered from COVID‐19 were more likely to be admitted to intensive care units than those with previously diagnosed diabetes 6 . Another study reported that those with newly diagnosed diabetes had a higher risk of progression to severe disease than those with pre‐existing diabetes among patients with COVID‐19 9 . However, these studies failed to adjust for pre‐admission glycemic status or to obtain information regarding adherence to diabetes care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, one study showed that patients with newly diagnosed diabetes who suffered from COVID‐19 were more likely to be admitted to intensive care units than those with previously diagnosed diabetes 6 . Another study reported that those with newly diagnosed diabetes had a higher risk of progression to severe disease than those with pre‐existing diabetes among patients with COVID‐19 9 . However, these studies failed to adjust for pre‐admission glycemic status or to obtain information regarding adherence to diabetes care.…”
Section: Discussionmentioning
confidence: 99%
“…Next, to analyze the modification effect of adherence to diabetes care on the association between COVID‐19 infection and HbA1c level, we used logistic regression and estimated the risk of an increase in the HbA1c level among individuals undergoing and not undergoing follow‐up for diabetes care in 2019. When we evaluated the modification effect of adherence to diabetes care on the association between HbA1c levels and COVID‐19 infection risk, we applied two methods: one in which HbA1c levels were categorized into HbA1c of 6.5–6.9%, 7.0–7.9%, and ≥8.0% 9 , and the other in which we applied a restricted cubic spline model with 3 knots, treating HbA1c levels as a nonlinear continuous variable with knots placed at 7%, 8%, and 10%. For the assessment of COVID‐19 infection risk, an HbA1c of 6.5–6.9% and 6.5% were set as references in the former and latter models, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms mentioned were proposed by Sathish et al [87] and some other authors [88,89]. Some studies showed that diabetes is related to prolonged hospitalization of patients with COVID-19 [90] and with worse disease outcomes [27,28,79,[91][92][93][94][95][96]. It is also concluded that patients with diabetes mellitus are more prone to developing severe symptoms of COVID-19 [28,93,94,96].…”
Section: Covid-19-induced Diabetesmentioning
confidence: 93%
“…It is also concluded that patients with diabetes mellitus are more prone to developing severe symptoms of COVID-19 [28,93,94,96]. Moreover, newly diagnosed diabetes during SARS-CoV-2 infection has been linked to an even worse prognosis than pre-existing, probably due to insufficient diabetes regulation [62,92,93,97].…”
Section: Covid-19-induced Diabetesmentioning
confidence: 99%